2004
DOI: 10.1111/j.0963-7214.2004.01501012.x
|View full text |Cite
|
Sign up to set email alerts
|

Mimicry and Prosocial Behavior

Abstract: Recent studies have shown that mimicry occurs unintentionally and even among strangers. In the present studies, we investigated the consequences of this automatic phenomenon in order to learn more about the adaptive function it serves. In three studies, we consistently found that mimicry increases prosocial behavior. Participants who had been mimicked were more helpful and generous toward other people than were nonmimicked participants. These beneficial consequences of mimicry were not restricted to behavior d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
411
1
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 593 publications
(446 citation statements)
references
References 15 publications
21
411
1
7
Order By: Relevance
“…Previous work has demonstrated that slightly asynchronous actions in capuchin monkeys can facilitate behavior similarity in a way that is equivalent to simultaneous action, a phenomenon known as isomorphic coordination (46). Capuchin monkeys are more affiliative and willing to interact with humans who have recently mimicked their actions (47), and mimicry increases prosocial behavior, affiliation, and a feeling of interconnectedness in humans (48)(49)(50). Mimicry, behavioral coordination, and synchronization may facilitate positive emotions and bonding, inducing state-matching between individuals, such as in emotional contagion (16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that slightly asynchronous actions in capuchin monkeys can facilitate behavior similarity in a way that is equivalent to simultaneous action, a phenomenon known as isomorphic coordination (46). Capuchin monkeys are more affiliative and willing to interact with humans who have recently mimicked their actions (47), and mimicry increases prosocial behavior, affiliation, and a feeling of interconnectedness in humans (48)(49)(50). Mimicry, behavioral coordination, and synchronization may facilitate positive emotions and bonding, inducing state-matching between individuals, such as in emotional contagion (16).…”
Section: Discussionmentioning
confidence: 99%
“…People may even be more inclined to vote for prosocial left-wing political parties following mimicry (Stel & Harinck, 2011). Taken together, these findings suggest that mimicry elicits prosocial responses which extend beyond the mimicry interaction (Van Baaren & Chartrand, 2005;van Baaren et al, 2004).Mimicry also appears to influence or affect the self-construal of the person being mimicked. When completing a 'twenty statements' measure of self-construal (Kuhn & McPartland, 1954), in which people may define themselves by relationships with other people (interdependently) or without reference to others (independently), people reliably provide more interdependent statements following mimicry (Redeker, Stel, & Mastop, 2011;Stel & Harinck, 2011;.…”
mentioning
confidence: 89%
“…The literature has identified situational (e.g., a goal to affiliate; , individual (e.g., a pro-social orientation; van Baaren et al 2003), and relational (e.g., group membership; Yabar et al 2006) variables that increase behavioral mimicry, and has shown that mimicry generally has positive consequences. For example, after mimicking somebody, individuals report higher liking of this person (Chartrand and Bargh 1999; and behave in a more pro-social fashion toward them and others (van Baaren et al 2004).…”
Section: Behavioral and Linguistic Mimicrymentioning
confidence: 99%